Upaya Guru IPS Dalam Mengembangkan Keterampilan Sosial Siswa di MTs Rogojampi Banyuwangi Tahun 2019 - Inayatul Umami; Musyarofah (Institut Agama Islam Negeri Jember, 2020)
Abstract Teachers in social studies (IPS) learning are not only required to provide knowledge to students in mastering concepts related to community and but also the environment. More than that IPS teachers are expected to be able to equip students to have social skills. The development of students' social skills needs to be pursued by a teacher, bearing in mind that social skills are one of the important competencies needed by students to be able to maintain good social relations with others. The purpose of this study is to explore the efforts of social studies teachers in developing students' social skills at MTs Rogojampi Banyuwangi which include communication skills; group building skills; and problem solving skills. This study employs a qualitative approach descriptive research. Determination of informants is done purposively. Data was collected through interviews, observation and documentation. In addition, the data was analysed using the interactive model of Miles Huberman and Saldana, and the validity of the data was done by triangulated the sources and methods. The results of the study show that social studies teachers 'efforts in developing students' communication skills are carried out by the students through resolving existing conflicts in subjects and in real life, students are accustomed to asking questions and expressing opinions, and are trained to be able to speak in public. The effort of social studies teachers in developing students' group building skills is done through group discussions in learning, giving group assignments, and inviting students to do community service outside of the lesson or at empty hours. The efforts of social studies teachers in developing students' skills to solve problems namely through discussion, providing them with problems to be resolved by students, having students position themselves as people who have problems, finding solutions and asking students to solve problems themselves and learning about responsibility. Abstrak Dalam pembelajaran IPS, guru tidak hanya dituntut untuk memberikan pengetahuan kepada siswa dalam menguasai konsep-konsep yang terkait kehidupan masyarakat dan lingkungannya. Lebih dari itu guru IPS diharapkan mampu membekali peserta didik memiliki keterampilan sosial. Pengembangan keterampilan sosial siswa perlu diupayakan oleh seorang guru, mengingat keterampilan sosial merupakan salah satu kompetensi penting yang dibutuhkan oleh seseorang untuk dapat menjaga hubungan sosial secara baik dengan orang lain. Tujuan penelitian ini adalah mendeskripsikan upaya guru IPS dalam mengembangkan keterampilan sosial siswa di MTs Rogojampi Banyuwangi yang meliputi keterampilan komunikasi; keterampilan membangun kelompok; dan keterampilan menyelesaikan masalah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Penentuan informan dilakukan dengan purposive. Data dikumpulkan melalui wawancara, observasi dan dokumentasi. Teknik analisis data menggunakan model interaktif Miles Huberman dan Saldana, serta keabsahan data dilakukan dengan triangulasi sumber dan metode. Hasil penelitian menunjukkan upaya guru IPS dalam mengembangkan keterampilan siswa dalam berkomunikasi dilakukan dengan siswa diajarkan untuk menyelesaikan konflik yang ada pada mata pelajaran maupun dalam kehidupan nyata, siswa dibiasakan untuk bertanya dan menyampaikan pendapat, serta dilatih untuk dapat berbicara di depan umum. Upaya guru IPS dalam mengembangkan keterampilan siswa membangun kelompok dilakukan melalui diskusi kelompok dalam pembelajaran, memberikan tugas kelompok, serta mengajak siswa melakukan kerja bakti di luar pelajaran maupun di jam kosong. Upaya guru IPS dalam mengembangkan keterampilan siswa untuk menyelesaikan masalah yakni melalui diskusi, guru memberikan masalah untuk diselesaikan siswa, menyuruh siswa memposisikan diri sebagai orang yang memiliki masalah, mencari solusi dan meminta siswa untuk menyelesaikan masalah sendiri dan belajar tanggung jawab. Kata kunci: Keterampilan Sosial, Upaya Guru, dan Ilmu Pengetahuan Sosial